Analysis of Computational Thinking Skills of Vocational School Students Based on Mathematical Literacy Skills in the Society 5.0 Era - Ainur Ayu Maulina; Hikmatul Khusna (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
Computational thinking skills are important and need to be developed in the 21st century. This study aims to describe the computational thinking ability of vocational school students based on mathematical literacy skills in the era of society 5.0. This research uses a qualitative descriptive method. This research was carried out at SMKN 1 Gunung Putri with research subjects namely students in grades XI RPL 1 and XI RPL 2 totaling 66 students. From the research subjects, 3 students were selected who had high, medium, and low mathematical literacy skills. The data collection technique was carried out using CT ability tests and CT ability interviews. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. This study shows that overall students' computational thinking skills are still relatively low because they have not mastered and applied all the indicators to the maximum. In students with high mathematical literacy skills, able to involve decomposition indicators, pattern recognition, algorithmic thinking, abstraction and generalization in type 1 and 2 problems. Students with moderate mathematical literacy skills are able to involve decomposition indicators, pattern recognition, and algorithmic thinking in type 1 and 2 problems. Students with low mathematical literacy skills, able to involve decomposition indicators and pattern recognition in type 1 and 2 problems, as well as algorithmic thinking indicators only in type 2 problems.